Preparation of TiO2‐Coated Mo Powders for High Photocatalytic Property. Issue 1 (8th October 2015) - Li, Delong; Wang, Miaosheng; Luo, Chengzhi; Pan, Chunxu
Abstract : An approach is introduced for fabricating the TiO2 ‐coated molybdenum (Mo) powders via hydrothermal method, in which the Mo nanopowders were prepared by the electric explosion of wire method. The microstructure and photocatalytic properties of the samples were characterized by X‐ray diffraction, scanning electron microscopy, high‐resolution transmission electron microscopy, Raman spectroscopy (Raman), low temperature sorption of nitrogen (BET), and diffuse reflectance accessory of UV–Vis spectrophotometer. It was revealed that compared with pure TiO2, the TiO2 ‐coated Mo powders exhibited an improved photocatalytic activity, and the highest photocatalytic activity was achieved at the 1 wt% optimal mass percentage of the Mo nanopowders. The preparation of TiO2 ‐coated Mo powders involved a relatively simple, economical, scalable, and also environment‐friendly approach.